Intracellular matrix metalloproteinase-2 (MMP-2) regulates human platelet activation via hydrolysis of talin - Soslau, Gerald; Mason, Christopher; Lynch, Stephen; Benjamin, James; Ashak, Dani; Prakash, Jamunabai M.; Moore, Andrew; Bagsiyao, Pamela; Albert, Trevine; Mathew, Lynn M.; Jost, Monika (Thrombosis and Haemostasis, 2014)
Matrix metalloproteinase (MMP) activity is generally associated with normal or pathological extracellular processes such as tissue remodeling in growth and development or in tumor metastasis and angiogenesis. Platelets contain at least three MMPs, 1, 2 and 9 that have been reported to stimulate or inhibit agonist-induced platelet aggregation via extracellular signals. The non-selective Zn+2 chelating MMP inhibitor, 1,10-phenanthroline, and the serine protease inhibitor, AEBSF, were found to inhibit all tested agonist-induced platelet aggregation reactions. In vitro analysis demonstrated that 1,10-phenanthroline completely inhibited MMP-1,2,and 9 but had little to no effect on calpain activity while the converse was true with AEBSF. We now demonstrate that MMP-2 functions intracellularly to regulate agonistinduced platelet aggregations via the hydrolytic activation of talin, the presumed final activating factor of glycoprotein (GP)IIb/IIIa integrin (the inside-out signal). Once activated GPIIb/IIIa binds the dimeric fibrinogen molecule required for platelet aggregation. The active intracellular MMP-2 molecule is complexed with JAK 2/STAT 3, as demonstrated by the fact that all three proteins are co-immunoprecipitated with either anti-JAK 2, or anti-STAT 3 antibodies and by immunofluorescence studies. The MMP-2 platelet activation pathway can be synergistically inhibited with the non-selective MMP inhibitor, 1,10-phenanthroline, plus a JAK 2 inhibitor. This activation pathway is distinct from the previously reported calpain-talin activating pathway. The identification of a new central pathway for platelet aggregation presents new potential targets for drug regulation and furthers our understanding of the complexity of platelet activation mechanisms.
Keywords: Matrix metalloproteinase; platelet physiology; thrombin; talin